Validitas LKPD Terintegrasi Augmented Reality Berbasis Inquiry Learning Pada Materi Klasifikasi Makhluk Hidup - Musa, Sri Novita; Lamangantjo, Chairunnisah J.; Mustaqimah, Nur; Latjompoh, Masra; Akbar, Muh. Nur (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Students' difficulties in understanding the concept of classification of living things, especially in grouping living things according to taxonomic levels and remembering scientific names, are the background to this study. Biology learning that tends to be teacher-centered and lacks direct interaction results in low student involvement in the scientific process. This study aims to develop and test the validity of Student Worksheets (LKPD) integrated with Augmented Reality (AR) technology based on the Inquiry Learning model as an interactive media to improve students' science process skills. The method used is research and development (R&D) with the ADDIE model, limited to the development stage. LKPD was developed based on a needs analysis at Wira Bhakti Gorontalo Integrated High School. Data were obtained through interviews with teachers and validation by media experts and material experts, which were analyzed descriptively quantitatively using a Likert scale. The validation results showed an average value of 86% (media) and 93% (material), both of which are included in the very valid category. Revisions were made based on validator input to improve visual aspects, content, and instructions for use. Thus, this LKPD is declared very valid and suitable for use as a learning medium to support students' science process skills in understanding the classification of living things.